The Prognostic Significance of RIMKLB and Related Immune Infiltrates in Colorectal Cancers - Cao, Yinghao; Deng, Shenghe; Yan, Lizhao; Gu, Junnan; Mao, Fuwei; Xue, Yifan; Qin, Le; Jiang, Zhengxing; Cai, Wentai; Zheng, Changmin; Nie, Xiu; Liu, Hongli; et al. (Frontiers in Genetics, 2022)
RimK-like family member B (RIMKLB) is an enzyme that post-translationally modulates ribosomal protein S6, which can affect the development of immune cells. Some studies have suggested its role in tumor progression. However, the relationships among RIMKLB expression, survival outcomes, and tumor-infiltrating immune cells (TIICs) in colorectal cancer (CRC) are still unknown. Therefore, we analyzed RIMKLB expression levels in CRC and normal tissues and investigated the correlations between RIMKLB and TIICs as well as the impact of RIMKLB expression on clinical prognosis in CRC using multiple databases, including the Tumor Immune Estimation Resource (TIMER), GEPIA, PrognoScan, and UALCAN databases. Enrichment analysis was conducted with the cluster Profiler package in R software to explore the RIMKLB-related biological processes involved in CRC. The RIMKLB expression was significantly decreased in CRC compared to normal tissues, and correlated with histology, stage, lymphatic metastasis, and tumor status (P<0.05). Patients with CRC with high expression of RIMKLB showed poorer overall survival (OS) (HR=2.5,P=0. 00042), and inferior disease-free survival (DFS) (HR=1.9,P=0.19) than those with low expression of RIMKLB. TIMER analysis indicated that RIMKLB transcription was closely related with several TIICs, including CD4+ and CD8+ T cells, B cells, tumor-associated macrophages (TAMs), monocytes, neutrophils, natural killer cells, dendritic cells, and subsets of T cells. Moreover, the expression of RIMKLB showed significant positive correlations with infiltrating levels of PD1( r=0.223, P=1.31e-06; r=0.249, P=1.25e-03), PDL1 (r=0.223, P=6.03e-07; r=0.41, P=5.45e-08), and CTLA4 (r=0.325, P=9.68e-13; r=0.41, P=5.45e-08) in colon and rectum cancer, respectively. Enrichment analysis showed that the RIMKLB expression was positively related to extracellular matrix and immune inflammation-related pathways. In conclusion, RIMKLB expression is associated with survival outcomes and TIICs levels in patients with CRC, and therefore, might be a potential novel prognostic biomarker that reflects the immune infiltration status.